KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA DITINJAU DARI SELF-REGULATED LEARNING SISWA DALAM MATERI LINGKARAN DI SMP - Desi Rohani; Zubaidah R; Bistari Bistari (Jurnal AlphaEuclidEdu, 2022)
This study aims to determine the ability to solve mathematical problems with the level of self-regulated learning in SMP Negeri 6 Pontianak. The method used in this research is descriptive with the type of qualitative research. The research subjects were grade IX G students who had studied the circle material. The results of data analysis show that students with high levels of self-regulated learning have good mathematical problem solving skills, namely being able to understand problems, plan solutions, implement plans, and re-examine the results obtained. Students with moderate levels of self-regulated learning have good mathematical problem solving skills, namely being able to understand problems, plan solutions, and carry out plans. Students with low levels of self-regulatory learning have low mathematical problem-solving abilities, only fulfilling the first problem-solving step, namely understanding the problem while planning solutions, implementing plans, and re-examining the results obtained by students with low self-regulated learning students have not been able to.